"It's gotta be done right way": a qualitative study exploring the acceptability of a proposed longitudinal cohort study of young Aboriginal children in Alice Springs - Catherine Lloyd-Johnsen; Angela Hampton; Emma Stubbs; Sam Moore; Sandra Eades; Anita D'Aprano; Sharon Goldfeld (BMC, 2023)
Abstract There is a need for quality longitudinal data on the health and well-being of young Aboriginal and Torres Strait Islander children (hereafter Aboriginal) in Alice Springs that can be used for research, planning and evaluation. The primary aim of this descriptive qualitative study was to determine whether or not a proposed cohort study would be acceptable to the local community. The proposed cohort study will prospectively examine various factors, events and exposures in early life that give Aboriginal children the best chance to grow up strong and lead a healthy happy life. Decisions on specific priority issues to be addressed and study procedures will be determined by local Aboriginal researchers and community members during a future co-design phase. 27 semi-structured interviews and 3 focus group discussions (FGD) were conducted with a range of community stakeholders and parents/caregivers of young Aboriginal children from Alice Springs in the Northern Territory (NT) of Australia. Audio recorded data were transcribed and imported into NVivo12 qualitative software for reflexive thematic analysis. Three major themes concerning acceptability of the concept were constructed from the analysis: (1) Have to be mindful, (2) Duplication of data, and (3) "It's gotta be done right way". There was general support for the concept, however, many participants felt that a cautious and slow approach was necessary. Recommendations included focusing on building trust, taking it slow, and ensuring the study is conducted by local Aboriginal researchers. Barriers to feasibility noted included the high mobility of families, competing demands, and privacy concerns. Findings from this qualitative study support the feasibility and acceptability of a future cohort study of young Aboriginal children in Alice Springs. Leadership from respected local Aboriginal researchers and key stakeholders will be critical to its success.